Resistome and virulome of multidrug-resistant Neisseria gonorrhoeae clinical isolates from Peru - Ana Jorge-Berrocal; Fabiola Salazar-Quispe; Yuli Janeth Barrios-Cárdenas; Henri Bailon-Calderon; Marco Galarza-Perez; Abraham Espinoza-Culupú (Scientific Reports, 2026)
Abstract Gonorrhea is a global public health issue, with the highest number of cases in Peru originating from Lima, the capital. This study conducted whole genome sequencing on 72 Neisseria gonorrhoeae isolates collected from various regions of Peru between 2018 and 2023 to characterize their resistome and virulome. Among these, 31 isolates displayed high-level azithromycin resistance (MIC ≥ 256 µg/mL). The analysis revealed significant resistance rates to ciprofloxacin (95.8%), penicillin (70.8%), tetracycline (68.1%), azithromycin (55.6%), and reduced susceptibility to extended-spectrum cephalosporins, observed in 4.2% for ceftriaxone and 9.7% for cefixime. Genetic diversity assessments identified multiple sequence types (STs) using MLST, NG-MAST, and NG-STAR methods. MLST revealed 16 distinct STs and one unassigned strain, with ST-9363 being the most prevalent (52.78%, 38/72), found in five out of seven departments. NG-MAST identified 22 STs, with 15 unassigned strains, highlighting ST-3935 as the most frequent (25.0%, 18/72). NG-STAR analysis discovered 35 STs, including 14 novel types, with ST-5804 accounting for 31.94% (23/72). The resistome analysis uncovered diverse mutations linked to antibiotic resistance, while the virulome analysis detailed various virulence factors facilitating infection, immune evasion, and disease propagation. Interestingly, some isolates lacked specific virulence genes. These findings provide critical insights into the genetic diversity, antibiotic resistance profiles, and virulence characteristics of N. gonorrhoeae strains circulating in Peru from 2018 to 2023, offering essential information to guide future control and prevention strategies.